2023
DOI: 10.1101/2023.01.28.525980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hub architecture of the human structural connectome: Links to aging and processing speed

Abstract: The human structural brain network, or connectome, has a rich-club organization with a small number of brain regions showing high network connectivity, called hubs. Hubs are centrally located in the network, biological costly, and might be critical for human cognition. Normal aging is accompanied by cognitive decline, including processing speed, and has been linked to energy depletion in the neurons at a molecular level. However, it is still unclear how age affects hub connections in human connectome. Using a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Overall, our model shows a transition occurring in midlife within the language connectome, that is a shift from a more “energy‐intensive” (costly) dynamic of compensation to a more “energy‐efficient” one. Indeed, our research indicates that younger adults are more capable of accommodating the metabolic demands associated with sustaining long‐range neural connections (Li et al, 2023; Liang et al, 2013; Tomasi et al, 2013). In comparison, older adults seem to adopt a more “energy‐efficient” approach, substituting the reallocation of long‐range connections between subsystems with short‐range connections within subsystems, thus lowering the metabolic demands needed to achieve compensatory integration.…”
Section: Discussionmentioning
confidence: 85%
“…Overall, our model shows a transition occurring in midlife within the language connectome, that is a shift from a more “energy‐intensive” (costly) dynamic of compensation to a more “energy‐efficient” one. Indeed, our research indicates that younger adults are more capable of accommodating the metabolic demands associated with sustaining long‐range neural connections (Li et al, 2023; Liang et al, 2013; Tomasi et al, 2013). In comparison, older adults seem to adopt a more “energy‐efficient” approach, substituting the reallocation of long‐range connections between subsystems with short‐range connections within subsystems, thus lowering the metabolic demands needed to achieve compensatory integration.…”
Section: Discussionmentioning
confidence: 85%
“…Relatedly, sensorimotor information (States 4-5) was more often redirected along a posterior route via visuo-occipital areas (States 3-6) to dorso-posterior states where DMN converges with lower-level circuitry (States 2 and 8). Acute engagement of the visuo-occipital regions in the alpha-band may thus facilitate information flow between sensorimotor and dorso-posterior DMN in older adulthood, hypothetically lowering the metabolic demands of maintaining long-distance functional connections 88 .…”
Section: Sensorimotor Integration Is Less Dynamic and Redirected Alon...mentioning
confidence: 99%
“…Compared with non-hubs, hubs are more densely interconnected, forming a rich-club organization (van den Heuvel & Sporns, 2011). Previous studies of structural brain networks found that connections of hubs were disproportionately influenced by development and aging (Baker et al, 2015;Li et al, 2023). In parallel, a recent study found that genes played a preferential role in shaping the connections between hubs (Arnatkeviciute et al, 2021).…”
Section: Age-related Changes In Local Organization Of Single-subject ...mentioning
confidence: 99%